Legal trasplant - Backenköhler Casajús, Christian J. (EUNOMÍA. Revista en Cultura de la Legalidad, 2019)
The legal transplant is a comparative law metaphor created to indicate the normative transfer that occurs between different legal systems. At first, the legal transplant served to demonstrate that, for a long time, the normative transfer was a mechanism frequently used to create new legal systems or, also, for the adaptation or renewal of many of them. Over time, however, it has developed into a concept which, apart from describing the transfer of a rule from one legal system to another, also seeks to explain the possible consequences that the receiving legal system may suffer. At present, legal transplant is serving to explain the normative transfer between different legal systems in the context of globalization and, also, as an indicator of the existence of legal pluralism in the current legal space.